Three-dimensional kinematic analysis of the Yurchenko layout with 360-degree twist in female vaults: deterministic model and judges' scores - Park, C-H.; Kim, Y.-K. (Korean Journal of Sport Biomechanics, 2017)
Objective: The purpose of this study was to identify kinematic variables that govern successful performance and judges' scores and to establish correlative relationships among those of Yurchenko layout with a full twist in female vaults. Method: Four video cameras with sampling rate of 60 Hz collected 32 motion data of Yurchenko vaults from twenty-two female participants (age: 18.6 ± 3.6 years, height: 153.0 ± 6.5 cm, mass: 44.7 ± 7.3 kg) during national competition. Posting processing and calculations of kinematic variables were performed in Kwon 3D XP and Matlab® programs. Correlation and regression analyses were applied to find the relationships between the obtained scores and kinematic variables. Deterministic model (Hay & Reid, 1988) was used to investigate the strength of correlative relationships among kinematic variables. Results: The obtained scores from the judges' decision were mainly affected by post-flight peak height, horse contact time, knee angle at landing, and horse takeoff angle. Strong blocking during horse contact was required to get successful performance and obtain high scores. Modified deterministic model showed that round-off entrance and takeoff angles and resultant velocity of the center of mass (CM) during the round-off phase were the starting variables affecting performance in the following kinematics. Knee angle at landing, a highly influential variable on the obtained point, was only determined by judges' decision without significant correlative relationship with previous kinematic variables. Conclusion: The obtained scores highly depended on kinematic variables of post-flight and horse contact phases that were affected by those from the previous phases including round-off postures and resultant velocity of the body center of mass.